Sistem Latihan Program Pembangunan dan Kepimpinan Pelajar (i-LPPKP) / Wan Mohd Hafiz Hakime Wan Hazemin - Wan Hazemin, Wan Mohd Hafiz Hakime (2011)
Nowadays, there are so many types of web applications to facilitate users in daily life. The main objective of this system is to develop a web based system to manage evaluation of students and facilitators in Latihan Program Pembangunan Dan Kepimpinan Pelajar (LPPKP). Currently, the administration side uses forms to evaluate students, facilitators and programmes. As a result, they have problems in organizing the data for Latihan Program Pembangunan dan Kepimpinan Pelajar (LPPKP) at FSKM. This is due to the evaluation marks was recorded manually into Microsoft Excel. The administration side should also record all information of LPPKP manually by using conventional form. Consequently, the evaluation forms of students and facilitators likely would be lost. By developing this system, the management side will be save their cost and time to print out the evaluation form. By using this system, the students and facilitators do no need to use manual method to give the feedback during module session but they just need to access the system and give the feedback. The security aspect will be implemented into this system such as password to enter this system. This system is using PHP programming languages and uses the MySQL for the database. In order to make the system can connect to the database, the researcher had installed Xampp version 2.5 that contains PhpMyAdmin for managing the database, Apache server and can make the interface to interact with the database using MySQL statements.